2016
DOI: 10.1117/12.2233711
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Meter Telescope narrow-field infrared adaptive optics system real-time controller prototyping results

Abstract: Prototyping and benchmarking was performed for the Real-Time Controller (RTC) of the Narrow Field InfraRed Adaptive Optics System (NFIRAOS). To perform wavefront correction, NFIRAOS utilizes two deformable mirrors (DM) and one tip/tilt stage (TTS). The RTC receives wavefront information from six Laser Guide Star (LGS) ShackHartmann WaveFront Sensors (WFS), one high-order Natural Guide Star Pyramid WaveFront Sensor (PWFS) and multiple low-order instrument detectors. The RTC uses this information to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Combining the 1024×1024 (rows×columns) inverse covariance matrix, 1024×3610 reference image matrix, and 3610×1 target image vector (the latter two are typically dotted to produce the target image correlation vector) into a single matrix operation produces a (1024 × 3610) · (3610 × 1) matrix multiplication. One Narrow Field InfraRed Adaptive Optics System (NFIRAOS) server processing one laser guide star wavefront sensor (WFS) multiplies a matrix of 7000×5400 by a 5400×1 vector in 500 µs, 15 and so our FAST approach should be less than this amount. Finally, the FFT cannot start before the last pixel is received, so adding a few hundred microseconds to read out the image yields (350 µs) + (less than 500 µs) + (about 200 µs) = (less than about 1.05 ms).…”
Section: Frameworkmentioning
confidence: 99%
“…Combining the 1024×1024 (rows×columns) inverse covariance matrix, 1024×3610 reference image matrix, and 3610×1 target image vector (the latter two are typically dotted to produce the target image correlation vector) into a single matrix operation produces a (1024 × 3610) · (3610 × 1) matrix multiplication. One Narrow Field InfraRed Adaptive Optics System (NFIRAOS) server processing one laser guide star wavefront sensor (WFS) multiplies a matrix of 7000×5400 by a 5400×1 vector in 500 µs, 15 and so our FAST approach should be less than this amount. Finally, the FFT cannot start before the last pixel is received, so adding a few hundred microseconds to read out the image yields (350 µs) + (less than 500 µs) + (about 200 µs) = (less than about 1.05 ms).…”
Section: Frameworkmentioning
confidence: 99%
“…The system architecture is based upon commercial server hardware with a classical Matrix Vector Multiply (MVM) control algorithm. Intensive benchmarking have been conducted to support this architecture and have demonstrated that the performance requirements can be met by using a moderate number of existing off-the-shelf commercial boards, which in addition enable the use of a significantly simpler RTC algorithm (MVM) [14], [15] .…”
Section: Real Time Controllermentioning
confidence: 99%
“…The most recent hardware benchmarking results point to CPUs and Intel Xeon Phi coprocessors being preferred over GPUs. 13,14 The European Southern Telescope (ESO) has also moved on from a combination of FPGAs and Digital Signal Processors (DSPs) for its AO RTC 15 to a heterogenous architecture involving CPUs and GPUs for mathematical processing and FPGAs for the high-speed interfacing. 16,17 A similar scalable AO kernel involving an FPGA-based Network Interface Card (NIC) for peer-to-peer communication, with GPUs performing the intensive computational part, is explored in Perret et al 18 A more recent approach from ESO (called Green Flash) aims to compare competing technologies of co-processors, GPUs and FPGAs for use as the computing platform for the AO system on the E-ELT.…”
Section: Introductionmentioning
confidence: 99%